2012
DOI: 10.1186/1556-276x-7-173
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial deposition of silver ultra-fine nano-clusters on defect-free surfaces of HOPG-derived few-layer graphene in a UHV multi-chamber by in situ STM, ex situ XPS, and ab initio calculations

Abstract: The growth of three-dimensional ultra-fine spherical nano-particles of silver on few layers of graphene derived from highly oriented pyrolytic graphite in ultra-high vacuum were characterized using in situ scanning tunneling microscopy (STM) in conjunction with X-ray photoelectron spectroscopy. The energetics of the Ag clusters was determined by DFT simulations. The Ag clusters appeared spherical with size distribution averaging approximately 2 nm in diameter. STM revealed the preferred site for the position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In particular, Ag nanowires can be used as electrosensors for amines [3], or as the basis for more sophisticated nanostructures synthesis with other applications. There are extensive experimental results of the Aggraphite system [4][5][6][7][8][9] as well as theoretical studies of Ag adsorption on graphite surfaces without defects [10][11][12][13][14][15][16]. These results are, at the same time, supported by scanning tunneling microscopy (STM) characterization of graphite substrates after Ag evaporation on this surface [17,18].…”
Section: Introductionmentioning
confidence: 55%
“…In particular, Ag nanowires can be used as electrosensors for amines [3], or as the basis for more sophisticated nanostructures synthesis with other applications. There are extensive experimental results of the Aggraphite system [4][5][6][7][8][9] as well as theoretical studies of Ag adsorption on graphite surfaces without defects [10][11][12][13][14][15][16]. These results are, at the same time, supported by scanning tunneling microscopy (STM) characterization of graphite substrates after Ag evaporation on this surface [17,18].…”
Section: Introductionmentioning
confidence: 55%
“…34 Coalescence was also observed for Ag clusters on HOPG where their mobility was attributed to a weak interaction with the substrate. 35 Previous studies have shown that the diffusion and coalescence of clusters at room temperature alter the cluster sizes in such a way that a broad cluster size distribution and reduced cluster density can be observed, especially at high coverage. 12,15 In contrast, an increase in cluster density with increasing coverage was seen for Pt on graphene/Ru(0001) 29 and for Ni on graphene/ Rh(111).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Most experimental studies of evaporated films of Ag (either from Ag monomers or from small, mass-selected Ag cluster ions) on graphite(0001) or graphene surfaces found that the Ag agglomerates into 3D clusters at room temperature, as we find here. 24,[38][39][40]46 One early STM study reports "flat" Ag clusters referred to as 2D clusters on graphite, but that study was performed at very low coverages (∼0.001 ML), 45 much lower than here.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…There have been many previous studies of the adsorption of gaseous Ag monomers and small clusters on graphite and graphene surfaces using both experimental methods , and theoretical methods , (typically density functional theory). While the exact results of these studies can vary tremendously with the methods used, there is some consensus that a weak interaction between Ag metal and the graphite support leads to the clustering of Ag monomers to form 3D particles. ,,,, Microscopy images show that these particles grow preferentially at the step edges when grown on graphite at room temperature and above. , …”
Section: Introductionmentioning
confidence: 99%